Peningkatan Hasil Belajar Ekonomi Dengan Menggunakan Model Pembelajaran Kooperatif Tipe Jigsaw Kelas XI IIS SMA Negeri 2 Palangka Raya - Redno Setiawan; Iin Nurbudiyani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to determine the learning activities of students and the results of learning economic economics by using the Jigsaw type cooperative learning model for students. This study is a Classroom Action Research (CAR). The subjects of this study were 34 students of class II-2 IIS-2 SMA SMA Palangka Raya. This data collection technique is observation and testing. Data analysis techniques using Qualitative and Quantitative. The results showed that the learning activities of students belonged to the good category and there was an increase in economic learning outcomes in students using the Jigsaw cooperative learning model in the Pre Test of 34 students who received a score of ≥78 reaching 8.82% ( 3 students) with an average value of 55, in the first cycle the results of the Post Test which obtained ≥78 reached 58.82% (20 students) with an average value of 73.08 and in the second cycle the results of the Post Test were scored ≥78 reached 100% (34 students) with an average score of 84.71.